The Role of IL-6 and TGF-β1 in Iraqi Women with Recurrent Abortion - Roua Jamal Abdulkhaliq (Journal of Global Pharma Technology, 2018)
The alteration in the cytokines stability synthesis by Thelper1 cells with a rise of interleukin 6 (IL-6) and Thelper2 cells with the increase of TGF-β1 secretion is measured critical for retaining of usual pregnancy and increased risk of recurrent spontaneous abortion (RSA). This study was designed to measure some cytokines and affect these cytokines in the case of recurrent spontaneous abortion and healthy pregnant. Blood samples were collected from 210 women 180 women with the recurrent pregnancy loss (three or more abortions), and 30 women with normal pregnancy to three or more birth and without a previous abortion in the first trimester Based on clinical examination and diagnostic laboratory findings for TORCH of ELISA examination measured serum levels of immunoglobulin (IgM and IgG (for Toxoplasmosis, cytomegalovirus, herpes, and rubella in normal pregnant and in aborted women. Depending on the results of the test, the patients were divided into four groups: group one included 30 women with recurrent abortion with seronegative for TORCH test was (23.8%), group two recurrent aborted with seropositive for anti-toxoplasma antibodies was (20.9%), group three included recurrent abortion suffering from infected with different causes such as (cytomegalovirus, Rubella or Herpes) ratio was (41%). while group four women with a healthy pregnancy promise as a control group was (% 14.3). Then taking thirty serum samples of women from the first and second group with recurrent abortion and compared with control group then measured serum levels of pro-inflammatory cytokines Interleukin-6 (IL-6) and anti-inflammatory marker Tumor growth factor-beta1 (TGF-β1). The results presented that the serum levels of (IL-6) were highest in group1 and 2 (474.50 pg/ml and 629.60 pg/ml) respectively compared with control group (247.03 pg/ml), there was a significant difference. While TGF-β1 was the highest level in group1 (217.63 pg/ml) followed by group 2 (171.06 pg/ml) then control group (109.97 pg/ml) with the significant difference between three groups. The results indicated that the serum levels of pro-inflammatory and anti-inflammatory marker found with high level in recurrent abortion compared with healthy pregnant.